Decentralization in Indonesia: An Evaluation of the Implementation of Laws 22 and 25 of 1999 - Beche bt Mamma (Department of International Relations, Universitas Andalas, 2016)
Indonesia has been undergoing a reform process. It started with the process of rapid decentralization government began in 1999 from a strong centralized system. One of its process is the introduction of decentralization, a process of transfer power from the central government to provinces to sub-provinces. Decentralization became a worldwide phenomenon since over three decade. Countries around the world use decentralization principles with varying degree, mostly by transferring responsibilities of public service delivery to lower levels of government. The decentralization literature promotes the good governance aspects associated with decentralization including local citizen participation, democratic elections and financial and political equity. Decentralization in Indonesia is much more of an administrative decentralization rather than a fiscal decentralization. The central government continues to control a vast share of the revenues required for local governance under true decentralization.Key words: Decentralization, Reform Process, Centralized System, Governance